A ordem internacional em transformação: uma análise em três dimensões - Oliveira, Ivan Tiago Machado (2017)
This article aims to analyze the changes in international order and its relation to the expansion of the meaning of internationalization, taking three dimensions into account: the vertical dimension of international relations (interstate); the relation between State and civil society; and the dynamics of the productive process.